Work-family psychological contract as a mediator in the relationships between work-family factors and organizational commitment - Mohamed Azim, Abdul Mutalib; Ahmad, Aminah; Omar, Zoharah (Center for Promoting Ideas, 2011)
Psychological contracts evolve or change over time as a result of changing needs of employees and employers. The dynamic changing demography of the workforce results in employees’ psychological contract with employer pertaining to employer’s assistance in managing employees’ work and family roles. This paper presents a conceptual model on the mediating role of work-family psychological contract in the relationships between work-family factors and affective organizational commitment. The model is developed based on the psychological contract theory as well as previous research findings. The proposed model has applied the global psychological contract concept to a more specific concept namely work-family psychological concept.